The partner - Grisham, John (Doubleday, Arrow Books, 1997)
They watched Danilo Silva for days before they finally grabbed him. He was living alone, a quiet life on a shady street in a small town in Brazil; a simple life in a modest home, certainly not one of luxury. Certainly no evidence of the fortune they thought he had stolen. He was much thinner and his face had been altered. He spoke a different language, and spoke it very well.